Effects of Japanese traditional herbal medicines (Kampo) on growth and virulence properties of Porphyromonas gingivalis and viability of oral epithelial cells. (29th August 2013) - Liao, James; Zhao, Lei; Yoshioka, Masami; Hinode, Daisuke; Grenier, Daniel
Abstract: Context : Kampos, commonly used in Japanese traditional medicine, are standardized herbal mixtures that have been used for centuries to treat a variety of ailments. We hypothesized that Kampos may have unidentified properties that may be beneficial in periodontitis, an inflammatory disease affecting the tooth-supporting tissues. Objective : The aim of our study was to investigate various Kampos and their natural ingredients for their effects on Porphyromonas gingivalis growth, adherence to epithelial cells and proteinase activity. In addition, their effects on oral epithelial cell viability were evaluated. Materials and methods : Growth inhibition of P. gingivalis by various Kampos and their natural ingredients was evaluated by a microdilution broth assay method. Their effects on P. gingivalis proteinase activity and adherence to oral epithelial cells were determined by fluorometric assays. The cytotoxicity of test compounds towards oral epithelial cells was evaluated by MTT [3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide] test. Results : Of the 27 Kampos tested, 7 were found to inhibit the growth of P. gingivalis . The lowest minimal inhibitory concentration (MIC) (250 µg/ml) was obtained with TJ-113. Analysis of the composition of the seven active Kampos showed that they contain Chinese rhubarb as a common ingredient. Therefore, additional growth inhibitory assays on P. gingivalis were carried out with purified anthraquinones known to be present in rhubarb. Aloe-emodin and rhein possessed the strongest antibacterial effects towards P. gingivalis with an MIC of 0.78 µg/ml. The seven Kampos containing rhubarb and purified anthraquinones also exhibited the capacity to decrease the adherence of P. gingivalis to oral epithelial cells and to reduce its proteinase activity. The most important anti-adherence effect of Kampo was obtained with TJ-126; at 250 µg/ml it reduced adherence of P. gingivalis to epithelial cells by 83%. Purified anthraquinones were found to be less active than Kampos. Kampo TJ-113 was found to be the most effective for inhibition of gelatin degradation (49% inhibition at 62.5 µg/ml). Again, purified anthraquinones inhibited gelatin degradation to a lesser extent. Lastly, none of the tested compounds showed cytotoxicity towards oral epithelial cells at the effective concentrations. Conclusion : Kampos containing rhubarb and its anthraquinone derivatives may represent promising molecules for controlling periodontal diseases through their capacity to inhibit P. gingivalis growth and virulence properties.